Cyathea fabiolae (Cyatheaceae, Polypodiopsida), a new scaly tree fern from the northern Andes - Tejedor, Adrian; Gallego, Luis Fernando Giraldo; Calatayud, Gloria; Lehnert, Marcus (Phytotaxa, 2022)
A new species of Cyathea is described for Peru and Ecuador. The new species differs from congeners by a combination of traits including glabrescent and scurfless mature axes abaxially, concolorous orange-brown petiole scales, winged costae, and lack of indusium. It is illustrated and compared to similar species, and its biogeography is discussed.